On the secular decay of the LARES semi-major axis. (November 2017) - Pardini, C.; Anselmo, L.; Lucchesi, D.M.; Peron, R.
Abstract: The laser-ranged satellite LARES is expected to provide new refined measurements of relativistic physics, as well as significant contributions to space geodesy and geophysics. The very low area-to-mass ratio of this passive and extremely dense satellite was chosen to reduce as much as possible the disturbing effects of non-gravitational perturbations. However, because of its height, about 1450 km compared with about 5800–5900 km for the two LAGEOS satellites, LARES is exposed to a much stronger drag due to neutral atmosphere. From a precise orbit determination, analyzing the laser ranging normal points of LARES over a time span of about 3.7 years with the GEODYN II (NASA/GSFC) code, it was found an average semi-major axis decay rate of −0.999 m per year, corresponding to a non-conservative net force acting nearly opposite to the velocity vector of the satellite and with a mean along-track acceleration of −1.444 × 10 −11 m/s 2 . By means of a modified version of the SATRAP (ISTI/CNR) code, the neutral drag perturbation acting on LARES was evaluated over the same time span, taking into account the real evolution of solar and geomagnetic activities, with five thermospheric density models (JR-71, MSIS-86, MSISE-90, NRLMSISE-00 and GOST-2004). All of them provided consistent results, well within their acknowledged uncertainties. Moreover, when the same models (JR-71 and MSIS-86) were used within GEODYN II in a least-square fit of the tracking data, the differences between the average drag coefficients estimated with SATRAP and GEODYN were of the order of 1% or less. Unlike what happened for the two LAGEOS, where Yarkovsky thermal drag and charged particle drag were the leading causes, it was found that neutral atmosphere drag alone was able to explain most (≈98.6%) of the observed semi-major axis decay of LARES. The remaining ≈1.4%, corresponding to an average along-track acceleration of about −2 × 10 −13 m/s 2 (i.e. ≈1/70 of neutral drag), was probably linked to thermal thrust effects. It was 50%, or less, of the value previously reported in the literature, but further and more detailed investigations, including the detection of the signature of the periodic terms, will be needed in order to characterize such smaller non-gravitational perturbation. Highlights: The neutral atmosphere drag perturbation on the LARES satellite was investigated. It was found to account for most of the observed semi-major axis decay. The results obtained with five atmospheric density models were mutually consistent. A further drag-like force was identified, about two orders of magnitude smaller. Detailed investigations will be needed to infer its origin (e.g. thermal thrust).